P58 Differential molecular diagnosis of uterine leiomyomas and leiomyosarcomas using DNA and RNA sequencing. (1st November 2019) - Mas, A; Alonso, R; Escorcia, P; Jimenez-Almazán, J; Monleón, J; Montero, B; Lago, V; Simón, C
Abstract : Introduction/Background: Nowadays, the absence of standardized criteria to identify and differentiate uterine leiomyomas (LM) and leiomyosarcomas (LMS) prior to surgery, cause a significant stress in the patient, leading to unnecessary invasive procedures and additional costs to the National Health System. As consequence, the development of an accurate and non-invasive differential diagnostic methods in patients with surgical indication is needed to avoid the potential dissemination of hidden LMS from morcellation. We aim to identify differential genetic targets in LMS vs LM using Next Generation Sequencing to advance our knowledge in their differential diagnosis. Methodology: A total of 13 LM and 13 LMS from formalin-fixed paraffin-embedded samples were collected, processed and targeted sequenced for DNA and RNA coding regions for 170 solid tumours associated-genes. DNA sequencing data were assessed to identify copy number variations (CNVs), single nucleotide variants (SNVs) and small insertions/deletions(indels). Through the RNA analysis we got the gene expression profile, splice variants and gene fusions, being validated by immunohistochemistry and fluorescence in situ hybridization. Results: Tumor mutation burden was higher in LMS vs LM specimens. In terms of CNVs, 20 genes in LMS vs 6 genes in LM were affected by deletions. Gains were also more frequently identified in LMS compared to LM (19 genes vs 3 genes). Regarding SNVs and indels, we identified 105 of 159 genes in LMS samples, while mutations in 82 genes were distinguished in LM samples. Specific transcriptomic profile was also observed for 11 genes of 55 in LMS samples, while 8.5% of initially diagnosed LMS showed high confidence gene fusions. Conclusion: This study represents a scientific-technological innovation that allows, through an integrated genomic and transcriptomic analysis, the discovery of novel genes and pathways that potentially differentiate LM vs LMS, providing a new insight for the molecular diagnosis that may shift the current therapeutic focus. Disclosure: Drs. Jimenez-Almazán and Simón are employed by Igenomix SL. The remaining authors report no conflict of interest.